Implementasi nilai-nilai Pancasila pada kegiatan pemberdayaan kesejahteraan keluarga (PKK) di desa Kuripan Ciseeng Bogor - Setiawati Setiawati; R. Dede Siswandi; Abdul Chaidir Marasabessy (Jurnal Ilmiah Mimbar Demokrasi, 2021)
This study aims to reveal the application of Pancasila values ​​in Family Empowerment and Welfare activities in Kuripan village. This study uses a qualitative method using a descriptive analysis approach. Data was collected through observation, interviews, and document studies. The conclusion of the research, 1) Precept I, that is, every activity and daily life is used to say greetings, beginning, and ending with prayer. Always work together in work groups, carry out worship together for Muslims. The basic principle is to respect the celebration of holidays for people of different religions. 2) Sila II, is an attitude of mutual cooperation, and there is no coercion for members 3) Sila III, which means doing community service, celebrating the independence day of the Republic of Indonesia, likes to wear batik 4) Sila IV, which means prioritizing freedom to express common interests, and everything is resolved through deliberation, and 5) Precept V, Do not separate seats, the application of a frugal lifestyle is supported by a socialization program about the importance of frugal living. The implementation of Pancasila values ​​in PKK activities in Kuripan Village is a subjective and objective implementation of Pancasila, because all activities carried out in PKK activities reflect the implementation of Pancasila values. Abstrak Penelitian ini bertujuan untuk mengungkapkan penerapan nilai-nilai yang terkandung dalam Pancasila yang tercermin pada kegiatan Pemberdayaan dan Kesejahteraan Keluarga di Desa Kuripan. Penelitian ini menggunakan metode kualitatif. Pendekatan penelitian yang digunakan ialah dengan analisis deskriptif. Untuk mengumpulkan data dilakukan dengan melakukan pengamatan, wawancara, dan studi dokumen. Kesimpulan hasil penelitian, 1) Sila I, dalam setiap kegiatan dan kehidupan sehari-hari digunakan untuk mengucapkan salam, diawali dan diakhiri dengan doa. Selalu bekerja sama dalam kelompok kerja, menjalankan ibadah bersama bagi yang muslim. Prinsip dasarnya adalah menghargai perayaan hari raya bagi umat yang berbeda agama. 2) Sila II, adalah sikap gotong royong, dan tidak ada paksaan untuk anggota 3) Sila III, yang berarti melakukan pengabdian kepada masyarakat, merayakan hari kemerdekaan Republik Indonesia, suka memakai batik 4) Sila IV, yang berarti mengutamakan kebebasan menyatakan kepentingan bersama, dan segala sesuatunya diselesaikan melalui musyawarah, dan 5) Sila V, tidak memisahkan tempat duduk, penerapan pola hidup hemat didukung oleh program sosialisasi tentang pentingnya tidak boros.